2008
DOI: 10.1007/s11136-008-9416-4
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific health-related quality of life questionnaires for heart failure: a systematic review with meta-analyses

Abstract: Most of the questionnaires studied met minimum psychometric criteria, though current evidence would primarily support the use of the MLHFQ, followed by the KCCQ and CHFQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
140
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(148 citation statements)
references
References 101 publications
3
140
0
5
Order By: Relevance
“…Quality of life assessed by means of the standard MLHF questionnaire remained at the same level for both modes and differences between the baseline and end of follow-up were not statistically signifi cant. This fact is surprising with respect to the signifi cant NYHA improvement mentioned above, since most of the MLHF questions are directly or indirectly related to physical functioning and correlate with the NYHA and 6-Minute Walk Test (6MWT) (26). Nevertheless, results of other studies concerning quality of life are very variable and do not always follow the above assumption.…”
Section: Discussionmentioning
confidence: 94%
“…Quality of life assessed by means of the standard MLHF questionnaire remained at the same level for both modes and differences between the baseline and end of follow-up were not statistically signifi cant. This fact is surprising with respect to the signifi cant NYHA improvement mentioned above, since most of the MLHF questions are directly or indirectly related to physical functioning and correlate with the NYHA and 6-Minute Walk Test (6MWT) (26). Nevertheless, results of other studies concerning quality of life are very variable and do not always follow the above assumption.…”
Section: Discussionmentioning
confidence: 94%
“…A systematic review with meta-analysis aiming to assess conceptual models and psychometric properties of five QoL assessment instruments for individuals with HF (MLHFQ, Chronic Heart Failure Questionnaire -CHFQ, Quality of Life Questionnaire for Severe Heart Failure -QLQ-SHF, KCCQ and Left Ventricular Dysfunction Questionnaire -LVD-36) showed that all had adequate psychometric properties, although there are concerns related to the construct validity of CHFQ and the response capacity of the QLQ-SHF (36) . Thus, QoL measurements used in studies included in this review can be considered reliable, since CHFQ and QLQ-SHF were not used by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, individualized education focused on disease self-management improves individuals' QoL (40) . This type of monitoring has good results due to low operational costs and easiness obtaining of information (36)(37)(38)(39)(40)(41) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed the score on the basis of the Minnesota Living with Heart Failure Questionnaire, which is one of the most widely used questionnaires to evaluate HF specific quality of life. 13,14) The score was calculated just before the administration of TLV and at 1 week after TLV treatment in all patients. The internal consistency among each item was sufficient (Cronbach's alpha, 0.766).…”
Section: Methodsmentioning
confidence: 99%